Analisis Faktor-Faktor yang Mempengaruhi Produksi Gambir di Kecamatan Sutera Kabupaten Pesisir Selatan - Almizan; Cahyani, Rahma; Ihsandi, Aslan Deri; Irsadunas (SAFE-Network, 2023)
Productivity and product quality are very low due to cultivation methods and post-harvest processes and gambier processing that are not optimal and the lack of technological support for gambier processing. The very low level of productivity causes the amount of production produced to also be low. The decrease in the value of gambier productivity indicates that there has been inefficiency of farmers in allocating existing production factors. This research is associative with a quantitative approach. The population in this study were 18,547 gambier farmers and the sampling technique was random sampling. So in this study using a sample of 100 respondents. This study uses Multiple Linear Regression Analysis with the help of SPSS version 25. The purpose of this study was to analyze the influence of the use of production factors in the form of land area, labor, gambier prices on gambier production. The results showed that the variables of land area and labor could increase the amount of gambier production positively and significantly. Gambier price variable has a positive and insignificant effect on the amount of gambier production.